P479 Reliability and responsiveness of histologic disease activity indices in Crohn's Disease. (30th January 2023) - Solitano, V; Schaeffer, D F; Hogan, M; Pai, R K; Zou, G; Pai, R K; Vande Casteele, N; Parker, C E; Remillard, J; Christensen, B; Panaccione, R; Sands, B E; et al.
Abstract: Background: The operating properties of histologic indices are poorly characterized in Crohn's disease (CD) and no validated index exists. We assessed the reliability and responsiveness of histologic indices/items, developed an exploratory index, and compared different methods of scoring. Methods: Using baseline and week 12 histologic image sets from the EXTEND placebo-controlled trial, blinded central readers scored 4 histologic indices (the Global Histologic Activity Score [GHAS], Geboes Score [GS], Robarts Histopathology Index [RHI], and Nancy Index [NHI]) and 3 additional novel items identified by an expert panel (mucin depletion, basal plasmacytosis, and pyloric gland metaplasia in the ileum). Reliability and responsiveness were evaluated for a global score (4 colonic segments + ileum), colonic score (4 colonic segments) and ileal score (ileum only) using the intraclass correlation coefficient (ICC) and area under the receiver operating curve (AUC), respectively. Change was defined using treatment assignment and improvement in histologic disease activity as measured on a 100-mm visual analogue scale (VAS) in responsiveness testing. Exploratory indices were developed using backward stepwise linear regression analysis. Candidate independent variables were items with an ICC ≥0.4 and AUC ≥0.56. The VAS served as the dependent variable. Results: Paired histologic images were analysed from 55 subjects. Inter-rater reliability was substantial to almost perfect (ICC=0.73-0.85) and responsiveness was small to large (treatment assignment AUC=0.50-0.65; VAS AUC=0.71-0.94). The GHAS, GS, RHI, and NHI reached the minimum threshold for reliability (ICC ≥0.4) and responsiveness (AUC ≥0.56) regardless of whether the global and colonic scores were calculated using the worst affected segment, average of the included segments, or sum of the included segments (Table 1-3). Five items were tested as candidate predictors. Three exploratory indices were developed, each consisting of 3 items: a global index (neutrophils in the lamina propria, neutrophils in the epithelium, and erosion/ulceration), colonic index (chronic inflammatory infiltrate, neutrophils in the lamina propria, and erosion/ulceration) and ileal index (chronic inflammatory infiltrate, neutrophils in the epithelium, and erosion/ulceration). The novel indices highly correlated with the GHAS, GS, RHI, and NHI, with correlation coefficients ≥0.80 (Table 4). Conclusion: The 4 existing indices were similarly reliable and responsive in measuring CD histologic activity, regardless of the method for calculating global and colonic scores and could be used in clinical trials. Attempts at novel index development did not offer benefit over current histologic indices.